Comparison of Gutta Percha Removal with Manual H-Files and ProTaper with or Without Eugenate - Nazish Iftikhar; Syed Muzammil Hussain; Fatima Tu Zahra; Maha Aslam; Aminah Sabir (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare manual H-File with ProTaper Retreatment files for the abolition of Gutta Percha filling material from the root canals with or without solvent use (Eugenate).